Drivers and Prerequisites for Digitalization for Public Companies A case study at Västtrafik - Engelbrektsson, Calle; Palmquist, William (My University, 2023)
It is crucial for today’s companies to handle the development of technology to stay relevant and competitive. The concept of digitalization is a growing trend, which when successfully conducted, strongly contributes to increased efficiency and sustainability of a company. Hence, affects a company’s relevance and competitiveness. Moreover, public companies struggle with conducting change initiatives and have a hard time keeping up with technology as compared to private companies. Therefore, the knowledge gap regarding digitalization for public companies is an area that needs to be investigated to create an understanding of drivers for digitalization as well as the required prerequisites. Hence, the purpose of this study is to understand why public companies need to digitalize, and what should be considered to prepare for digitalization. The study aims to gain an understanding of public company's approach to digitalization, as well as to assess the current situation and develop recommendations for how to prepare for a potential digitalization. To fulfill the purpose of the study, a qualitative case study was conducted at Västtrafik. Drivers and prerequisites for digitalization were identified through interviews and observations and later confirmed in a document analysis for one of the company’s main processes. The empirical data was analyzed through thematic analysis, where the results were put in relation to the theoretical framework. The conclusion showed that it is important for public companies to understand why they need to digitalize and the obvious relationship to efficiency and sustainability, as well as the needed prerequisites in terms of what should be considered to increase the chances of digitalization success. In conclusion, resource-demanding processes, difficulties in conducting, navigating and following up the process, as well as unclear responsibilities and a loss of control was identified as drivers for digitalization. Moreover, ability to allocate resources, capabilities to change, and standardized processes was identified as prerequisites for digitalization. Recommendations for Västtrafik were developed and divided into different steps regarding how to proceed with the process of preparing for a digitalization.
Keywords: public companies; digitalization; competitiveness; efficiency; sustainability; standardization; Lean; change management